Vehicle dynamics and stabilisation using a nonlinear tyre model with four–wheel steering and braking. (4th August 2014) - Lin, Hsi–Fu; Seireg, Ali A.
A dynamic vehicle simulation and control algorithm are developed in this study which utilise a nonlinear tyre model and coordinated four–wheel steering and braking systems to improve vehicle directional stability, controllability and response to driver's command on different road conditions. The linear programming algorithm is utilised for the evaluation of the distribution of the normal forces on the tyres and the optimum tractive/braking forces required for ensuring stability. The computer simulation of the developed four–wheel steering and braking system shows that the proposed approach can considerably enhance the stability and robustness of the performance of the vehicle especially under slippery road conditions.